EYALET OF NIŠ DURING THE ALBANIAN REBELION 1843–1844 (Heritage, 2024)
The paper presents a reconstruction of the Albanian rebellion (1843–1844) with a focus on the analysis of its final phase which took place on the territory of the Eyalet of Niš. In order to better understand the Albanian movement chronologically and territorially, its key moments in other parts of Rumelia are presented and then their connection and reflection on the events in Eyalet of Niš. Having presented the problem in this way, the paper points to two important conclusions: that the Albanians in the Ottoman Empire during the first half of the 19th century did not reach the political maturity which was necessary for the realization of their political goals, and that, due to the complex political conditions and relations between the central and local authorities towards the Christians in the Eyalet of Niš, Albanians with their revolt actually accelerated the resolution of issues which were of key importance for the Christians in this Ottoman province.
Keywords: Arnauts, revolt, Tanzimat, Niš, Vranje, Toplica, Kuršumlija, Leskovac, Skoplje, Kosovo